Youthʼs first job: desirable scenarios and real practices - E.A. Shinkarenko (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2022)
Background. The problem of youth adaptation in the labor market remains one of the urgent problems of Russian society caused by the transformations of professional and educational structures. The purpose of the work is to analyze the real and desired practices of the first employment of young people. Materials and methods. It is based on the materi-als of the authorʼs empirical research on the analysis of documents (electronic resumes of young people aged 18–25 on the HeadHunter portal). When considering the practices of the first employment, two conditional groups are identified: those who are looking for their first job and those who already have first job experience. Attention was paid to the presence of a diploma when applying for a first job, entry into the labor market was recorded before graduation or in the year of graduation. For young people who are looking for their first job, the qualification and job preferences of employment have been identified. For the se-cond group, the real experience of the first job is described. Results. At the stage of the first employment, most of the requests of young people, regardless of the level of education, are focused on positions of higher qualifications. When entering the labor market, motives are adjusted, which is reflected in employment in positions not of higher but of average qualifi-cations. The analysis of the first work experience indicated in the resume showed that uni-versity graduates occupy positions of higher qualification more often than graduates of vo-cational schools. Conclusions. When looking for a first job, young people adhere to both the strategy of gaining experience in their specialty in the skilled labor sector and the sce-narios of part-time jobs in positions of lower qualifications. The economic and socio-professional motives of employment are highlighted. Economic dominates in the low-skilled labor sector. Social and professional motives are visible in the desire to occupy posi-tions of higher and secondary qualifications at the start of a career, there is a focus on pro-fessional implementation in the intellectual labor sector.